Visual Outcome of Pediatric Traumatic Cataract in Lumbini Eye Institute, Bhairahawa, Nepal - Gurung, Govind; Bajracharya, Kabindra (Nepalese Journal of Ophthalmology, 2020)
Introduction: There are not many studies of pediatric trauma in Nepal. Therefore, this study was conducted to find out the visual outcome of pediatric traumatic cataract and causes of poor visual acuity. Materials and Methods: In this hospital based prospective study, all children visiting the pediatric department of Lumbini Eye Institute and Research Center with traumatic cataract and visual outcome after surgery from July 2018 to August 2019 were evaluated. A total of 136 children ranging from age (0 months to 15 years) with traumatic cataract were included in the study. Data on age of presentation, sex and diagnosis were collected from clinical charts and analyzed. Results: The study enrolled 136 cases with traumatic cataract. 72.1% male and 27.9% female patients were involved with the average age being 9.46 years (SD 2.95). Final visual acuity was better than 20/60 in 73 percent of the children. Visual acuity was poor in 27 percent of children. In children with poor visual acuity 44 percent of the patients had corneal opacity, 23 percent had retinal detachment and 18 percent had vitreous opacification secondary to trauma. Closed globe injury was seen in 72 percent of children and 28 percent had open globe injury. Conclusion: Male children were more prone to traumatic cataract than female children. Open globe injury with corneal laceration and opacity was the major cause of decreased visual acuity.